An analytical model for the effective filtration efficiency of single and multiple face masks considering leakage. (November 2021) - Boraey, Mohammed A.
Highlights: A model for the filtration efficiency of multiple face masks is developed. The model results were verified experimentally. Recommendations for double masking is given. Double masking is only beneficial for low leakage ratios. Double masking is more beneficial if the two masks are similar in efficiency. Abstract: An analytical model for the filtration efficiency of face masks is developed. The model considers the effect of gap leakage due to the improper fitting of the face mask in the reduction of the effective filtration efficiency. The model is also extended to include the case with multiple face masks. The model results are verified using experimental data from literature. It is shown that the adverse effect of the gap leakage depends on the face mask filtration and leakage characteristics. It is also shown that wearing more than one face mask might not always be beneficial in some scenarios. Recommendations on the best practice in the case of wearing two face masks are given.